Smuggling tourism in the North of Portugal and Galicia - Liberato, Pedro (2020)
This research, which presents a qualitative methodology, has as main objective, to understand how smuggling is being remembered and portrayed today, and which strategies can be proposed by entities, to promote smuggling as one of the main tourism resources in the North of Portugal. The main findings focus on the need for the organizations to invest in this new tourism product, as well as denoting the existing constraints, concluding about the success factors for this new tourism product in the border region. To promote it, and visioning its success, the interviewees suggest the development of diversified routes along the border, because this product differentiates himself from others for it genuineness, influence the population of the border to participate more actively in the routes, to share their memories, and build new authentic experiences not previously known by tourists.